Governança Local e Democrática em Dois Municípios da Grande Florianópolis: estudo sobre Conselhos Municipais e Políticas de Sustentabilidade - Sérgio Luís Boeira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2007)
The subject of this article is democracy and the administrative decentralization process in the area of Florianopolis, with emphasis to Florianópolis and São José, an adjacent city. In January of 2003, the State Government of Santa Catarina, under the management of Luiz Henrique da Silveira (PMDB), started implementing a new administrative reform with focus on decentralization. A big structural and legislative change has been happening since then with new institutions, such as the Regional Development Councils and the Regional Development Divisions. The research aimed at finding out if there are local government structures in good conditions to support the decentralization process, that is, to find out which City Councils are working and what their main administrative, social and political characteristics are. The City Councils represent the possibility of participative democracy expansion and qualification, expressing civic culture (social capital). The research was qualitative, descriptive and exploratory, as well as interpretative. The study showed, among other things, that there is a lack of information about City Councils among the government organs in the region, and not only among civil society organs. The cities of Florianópolis and São José are the only exceptions.